THE DEVELOPMENTOF YOUNG SCHOOL CHILDREN THROUGH THE PSYCHOMOTOR ACTIVITY - Pasăre Daniela; Raţă Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article presents the main reason for the choice of this topic which is based on the main theme: it researches the relation between music and movement, the implications of the formation of the intelligence of movement within the educational framework for the preadolescent children.